Apocalyptic Trends in Contemporary Politics - Marega, Stella (San José: Universidad de Costa Rica, Escuela de Estudios Generales, 2017)
The symbol of apocalypse contains strong political connotations linked to eschatological expectations: the faith in a divine intervention on the course of history has often generated social instability, outbreaks of violence, and ideological claims.This article aims to demonstrate as the overlap between apocalyptic symbolism and political phenomena is still ongoing, even assuming new critical implications in connection with recent geopolitical dynamics on a global scale.The detection of the apocalyptic trends is supported by a historical premise, a brief summary of theoretical perspectives, and three study cases: the presence of messianic aspects in US imperialism, the influence of the doctrine of the Hidden Imam in the Iranian politics during the Ahmadinejad presidency, and the use of apocalyptic prophecies in the Islamic State’s propaganda